THE ORIGINS OF RELIGIOUS TOLERANCE IN CENTRAL ASIA - Nematullo Mukhamedov; Nurulloh Turambetov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2021)
Tolerance is especially important today in the Central Asian region. This is because, firstly, today representatives of 16 confessions and more than 130 nationalities live on the territory of the Republic of Uzbekistan. Uzbekistan is a multi-confessional and multi-ethnic state. Secondly, since ancient times, the Great Silk Road passed on the territory of Uzbekistan, which stimulated the process of mutual communication and mutual influence of various national and religious cultures. Since ancient times, religions such as Buddhism, Christianity, Judaism and Islam have coexisted on our land. This article examines the historical and modern foundations of religious tolerance in the Central Asian region. The UN resolution “Enlightenment and Religious Tolerance”, adopted at the initiative of Uzbekistan, and its significance are disclosed. Also, on historical examples, the activities of various religious confessions operating on the territory of Uzbekistan, and universal values, such as tolerance and solidarity between them, are analyzed.